Attitudes and perceptions of dental students in Tamil Nadu state toward their curriculum and profession - Sharath Asokan; Baby John; P R Geetha Priya; N Bharathi (Wolters Kluwer Medknow Publications, 2014)
Background: Medicine and engineering still seems to be the most chosen career and the decision in the choice is largely influenced by the parents. Right attitude toward the chosen profession and the perceptions about the existing curriculum are important for any student to be successful in the college as well as in the career. Materials and Methods: A descriptive cross-sectional study was carried out among 466 undergraduate (bachelor of dental surgery) students from randomly chosen dental colleges in Tamil Nadu to assess their attitude and perception toward their curriculum and profession. A validated closed ended questionnaire with 18 questions was used in this study. The information obtained were: Reason to opt for the dental course, the most-hated part of the curriculum, adequacy of lecture and clinical hours, number and duration of lecture classes and clinical hours preferred, reason for not liking a particular subject, and the most important factor to be considered to rate a teacher. The proportion of the response was calculated to assess the overall attitude and perceptions of the students. Results: Forty-two percent of the students opted for the dental course because they did not get admission to the medical course. Written assignments (52%) were the most hated part of their curriculum. -42% of the students believed that the ideal attendance percentage should be 75%. Knowledge and teaching skills (79%) was the most important factor that was considered to rate a teacher. Conclusion: Majority of the students developed passion toward their profession. There was no serious complains about the existing curriculum, but a newer education model that can enhance the problem solving, and critical evaluation skills of the student is warranted.